La transparencia en la gestión de los recursos naturales. Una mirada regional para transformar la riqueza en desarrollo y evitar la corrupción - Huapaya Nava, Mario (2021)
Extractive companies, and their revenue management, are particularly exposed to acts of corruption. The challenges for this industry to become a generator of development are enormous but not impossible. Governments must work to protect and promote the development of extractive companies in a sustainable way, without corruption. To achieve that, the international community agrees that improving public institutions and strengthening relationships and trust of the actors that govern and interact in the sector is essential. This paper addresses two recommendations for that goal: information transparency and better and more transparent state companies in the Extractive Sector.